2005
DOI: 10.1097/00019514-200501000-00006
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Critical Paths

Abstract: A critical path defines the optimal sequencing and timing of interventions by physicians, nurses, and other staff for a particular diagnosis or procedure. Critical paths are developed through collaborative efforts of physicians, nurses, pharmacists, and others to improve the quality and value of patient care. They are designed to minimize delays and resource utilization and to maximize quality of care. Critical paths have been shown to reduce variation in the care provided, facilitate expected outcomes, reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(74 citation statements)
references
References 0 publications
0
68
1
5
Order By: Relevance
“…Coffey et al reported that the timely analysis and management of variance from a critical pathway can bring about improvements in the form of fewer complications and less resource consumption. 8,9 Members of a multidisciplinary team review the charts at irregular intervals, collect data to analyze variances retrospectively, and strive to improve the management process; however, managing variance also requires ongoing perseverance and dedication, and it remains unclear how often teams should meet and what improvements need to be implemented. 8 According to clinical pathway maintenance, it is rarely discussed literally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffey et al reported that the timely analysis and management of variance from a critical pathway can bring about improvements in the form of fewer complications and less resource consumption. 8,9 Members of a multidisciplinary team review the charts at irregular intervals, collect data to analyze variances retrospectively, and strive to improve the management process; however, managing variance also requires ongoing perseverance and dedication, and it remains unclear how often teams should meet and what improvements need to be implemented. 8 According to clinical pathway maintenance, it is rarely discussed literally.…”
Section: Discussionmentioning
confidence: 99%
“…To solve these data management problems, it is important to defi ne key measures of conformance and outcomes, which identify the key processes, decision criteria and outcome measures. 9 These measures include compliance with the clinical pathway, timeliness, and types of variations from the pathway. 9 The processes for development and use of the clinical pathway vary among organizations and management of variance differs among organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated care pathways (ICPs) are designed to standardise and guide management of whole episodes of medical illness (Coffey et al, 1992). Detailed guides to formulating optimal sequencing and collaborative multi-disciplinary efforts for people with AN are starting to appear.…”
Section: Anorexia Nervosa: Components Of Treatmentmentioning
confidence: 99%
“…14 The advantages of clinical pathways include reduced delays, lower length of stay and less variation in treatment. 14,17,18 What clinical pathways are available?…”
mentioning
confidence: 99%